ANALISIS KESALAHAN BERBAHASA PERCAKAPAN GRUP WHATSAPP MAHASISWA KELAS B LINGUISTIK TERAPAN UNJ ANGKATAN 2023 - Hamid B, La Ode Muhammad Idrus; Anwar, Miftahulkhairah (PT. Anagata Sembagi Education, 2024)
This study aims to analyze language errors that occur in student WhatsApp group conversations in order to improve understanding and use of language more effectively in the academic environment. This study uses descriptive qualitative method and data collection technique, which is sourced from language errors in WhatsApp grub of Applied Linguistics Doctoral Program UNJ Batch 2023 class B students. The results of this study show that there are a number of language errors that appear in the WhatsApp group conversations of Applied Linguistics Doctoral Program UNJ class 2023 students. The errors include aspects of spelling, capitalization, and improper writing. In various contexts and domains, these language errors occur because the Applied Linguistics Doctoral Program students of Batch 2023 class B use informal language when communicating in the WhatsApp group, which is a non-formal situation among their peers. These language errors can be attributed to the relaxed situation in which the doctoral students express their opinions by using more relaxed and informal language in their daily interactions in the group.